2021
DOI: 10.1200/jco.2021.39.15_suppl.e18544
|View full text |Cite
|
Sign up to set email alerts
|

First data from OUT: The National Cancer Survey of LGBTQ+ survivors.

Abstract: e18544 Background: Cultural barriers that inhibit LGBTQ cancer care are a public health crisis. Although LGBTQ cultural competency trainings are rapidly becoming the norm, patient-centered information is lacking for healthcare professionals in cancer care. The purpose of OUT: The National Cancer Survey is to understand the experiences of LGBTQ cancer survivors in order to make cancer care a safer and more welcoming place for survivors and their support teams. Methods: Individuals age 18 or older currently liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We know that people of all genders and sexualities who are diagnosed with cancer have additional unmet needs, and efforts to address the sexual health concerns of minoritized populations are urgently needed, including the concerns of those who identify as nonbinary. 6 Cancer-related sexual and reproductive concerns need to be approached using a coordinated and comprehensive biopsychosocial model that addresses biological, psychological, interpersonal, and sociocultural factors. These items would ideally be able to be personalized and delivered via close partnerships between cancer survivors and multidisciplinary teams using an integrated approach.…”
Section: + Related Articlementioning
confidence: 99%
“…We know that people of all genders and sexualities who are diagnosed with cancer have additional unmet needs, and efforts to address the sexual health concerns of minoritized populations are urgently needed, including the concerns of those who identify as nonbinary. 6 Cancer-related sexual and reproductive concerns need to be approached using a coordinated and comprehensive biopsychosocial model that addresses biological, psychological, interpersonal, and sociocultural factors. These items would ideally be able to be personalized and delivered via close partnerships between cancer survivors and multidisciplinary teams using an integrated approach.…”
Section: + Related Articlementioning
confidence: 99%
“…The National LGBT+ Cancer Network queried SGM patients' cancer care experiences in their online Out Survey, which sampled over 3,700 respondents. 16 The findings from the survey indicate that 81% of respondents felt they were respected and 89% felt welcomed during their cancer journey. 16 Although 87% of respondents felt their cancer center was safe for SGM patients, over 10% did not feel safe.…”
Section: Quality Improvement Strategiesmentioning
confidence: 95%
“…16 The findings from the survey indicate that 81% of respondents felt they were respected and 89% felt welcomed during their cancer journey. 16 Although 87% of respondents felt their cancer center was safe for SGM patients, over 10% did not feel safe. 16 The report also suggests disparities in crucial areas of care such as fertility preservation, with over 80% of respondents failing to recall any fertility discussions during their cancer care.…”
Section: Progress To Datementioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, many transgender, nonbinary, and genderexpansive people have had negative prior experiences with healthcare providers including being intentionally called by the wrong name or pronouns, experiencing verbal or physical abuse, and being refused care due to their transgender identity. In national surveys, 30% of transgender respondents reported delaying or avoiding medical care due to prior discrimination (8), and 24% of transgender cancer survivors reported that their oncology providers were not aware of their gender identity (9). Transgender and gender-expansive people experience healthcare disparities and may have unique needs (10).…”
Section: Introductionmentioning
confidence: 99%